Citizen Engagement in Operations : A Stock-Take of Citizen Engagement in Development Policy Financing - Kumagai, Saki (World Bank, Washington, DC, 2020)
Guided by the 2014 Strategic Framework for Mainstreaming Citizen Engagement in World Bank Group Operations, the World Bank supports policies, programs, projects, and advisory services and analytics where citizen engagement (CE) can improve development results. While the corporate commitment to mainstream CE targets investment operations, the World Bank teams continue to explore CE in other instruments. Engaging Citizens for Better Development Results, a report by the Independent Evaluation Group (IEG), assessed the Bank Group’s efforts to mainstream CE. It recommends the World Bank “encourage and support efforts of its regional, country, and Global Practices teams to establish, where appropriate, thick CE that is regular and continuous, uses multiple tools, and is embedded in country systems.” It also suggests this objective could be achieved by more systematically using existing channels of dialogue and stakeholder engagement, including that of Development Policy Financing (DPF), and applying tools at the various levels. Given this context, this Governance Note aims to take stock of existing CE practice in DPF by shedding light on the prior action usage.